Penerimaan DHIS2 oleh Sumber Daya Manusia Kesehatan di Kabupaten Kulon Progo - Lia Achmad (Jurnal Sistem Informasi Kesehatan Masyarakat, 2021)
To overcome the problem of data disintegration, the Ministry of Health through Pusat Data dan Informasi Kesehatan (Pusdatin) working together with UGM and the University of Oslo (UiO) to do implementation pilot of Aplikasi Satu Data Kesehatan (ASDK) with platform DHIS2 (District Health Information System 2. In the province of Yogyakarta (DIY), there is the health office of Kulon Progo Regency as the pilot of the implementation of DHIS2. It is necessary to be reviewed how the acceptance of DHIS2 by health human resource in Kulon Progo.Methods: Research used is non-experimental quantitative research with a cross-sectional study design. The research subject is all staff of the health Office of Kulon Progo Regency. Data retrieval after the respondent following the demo application DHIS2, FGD, and interviews. Analysis of data used for univariate is using the top 2 boxes and grouped into positive and negative categories, carried out the relationship test Rank Spearman and to support quantitative analysis results then discussed with the results of interviews and FGD.Results: The results obtained are performance expectancy, effort expectancy, social influence and facilitating condition have a significant relationship to the behavioral intention. Then in behavioral intention obtained only 10%. But in the performance variable expectancy obtained positive results about the perception of respondents to the usefulness of DHIS2 when implemented in the district of Kulon Progo is 62%. Respondents had a great expectation of the DHIS2's usefulness but had low intentions of use. It is explained with the results of FGD and interviews where leadership has a role in behavioral intention by staff and there is a different point of view regarding the desire to use DHIS2 between structural officers and staff.Conclusions: Assessment on performance expectancy tends to be positive with a percentage of 62% while in behavioral intentions only by 10% (with 71% of respondents having an assessment in the neutral to positive range), it is motivated by leadership factors (no direction from structural officials to use DHIS2 after attending DHIS2 workshop, absence of head of health office in the last year period), the number of health applications applied with limited human resources in the health service, understanding of DHIS2 as a new system. Keywords: UTAUT, Behavioral intention, DHIS2, Acceptance